Optimization of a cape gooseberry colloidal system for the micro-encapsulation process (2024)
Cape gooseberry is a fruit that contains various active compounds such as vitamins A, B, and C, proteins, minerals, tocopherols, and carotenoids, among others, which provide health benefits. The objective of this research was to experimentally optimize a colloidal system formulation based on cape gooseberry, gum arabic (GA), and maltodextrin (MD) (SCU+GA+MD) with the purpose of being subsequently used in a spray-drying micro-encapsulation process to protect and preserve its active components. A shear homogenizer colloid mill type was employed for the colloidal system preparation. The formulation design was conducted using a face-centered central composite design (α = 1), considering the independent variables: GA (1.0- 3.0%) and MD (9.5-13.5%), and the dependent variables: total solids (TS), viscosity (μ), zeta potential (ζ), particle size (D[4,3]), total phenols (TF), and antioxidant capacity (DPPH and ABTS assays). The optimal formulation was achieved with MD: 12.3% and GA: 3.0%, where the dependent variables were: TS: 32.2±0.1%, μ: 581.0±7.8 cP, ζ: -22.6±0.6 mV, D[4,3]: 77.9±2.0 µm, TF: 97.2±1.1 mg GAE 100 g-1, DPPH: 12.6±1.4 mg TE 100 g-1, ABTS: 13.5±0.6 mg TE 100 g-1. Experimental validation of the shear homogenization process for an integral colloidal system of cape gooseberry confirmed its physicochemical stability with significant solid content, rendering it suitable for spray-drying micro-encapsulation processes.